2002
DOI: 10.1021/ie0200510
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Phenol by the Pd/Mg and Pd/Fe Bimetallic Systems under Mild Reaction Conditions

Abstract: Three palladium-catalyzed zerovalent metal systems were found to be able to hydrogenate phenol to cyclohexanol and cyclohexanone under room temperature and pressure conditions. Exposure of 5.0 mM aqueous phenol solutions to Pd (2.6 ppt m/m)/Mg (1.00 g 20 mesh) and to 0.53 g of 1/8 in. Pd (0.5%)/alumina in contact with 1.00 g 20 mesh Mg results in 74% and 24% destruction of the reactant after 6 h of reaction time. The latter system was found to be greatly enhanced in the presence of 2% (v/v) glacial acetic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The fifth reaction cycle could achieve only 70% dechlorination of DDT accompanied by total dissolution of magnesium granules after 6 h. At this stage, non-availability of Mg 0 seemed to be limiting the progress of dechlorination reaction. Morales et al examined the potential of Pd 0 -alumina in combination with magnesium and iron to hydrogenate phenol [18]. They compared the hydrogenation capacity of Pd 0 pellets in absence and presence of acid.…”
Section: Dechlorination Of Technical Ddt Mixture Using Mg 0 -Pd 4+ Symentioning
confidence: 99%
“…The fifth reaction cycle could achieve only 70% dechlorination of DDT accompanied by total dissolution of magnesium granules after 6 h. At this stage, non-availability of Mg 0 seemed to be limiting the progress of dechlorination reaction. Morales et al examined the potential of Pd 0 -alumina in combination with magnesium and iron to hydrogenate phenol [18]. They compared the hydrogenation capacity of Pd 0 pellets in absence and presence of acid.…”
Section: Dechlorination Of Technical Ddt Mixture Using Mg 0 -Pd 4+ Symentioning
confidence: 99%
“…Although Fe 0 has been applied extensively for remediation of several pollutants, the major drawbacks are slow reaction rates, rapid passivation of the metal and requirement for strict anaerobic conditions. In comparison, magnesium metal (Mg 0 ) exhibits superior performance and has been used in combination with palladium, an excellent hydrogenation catalyst for the successful and rapid dechlorination of DDT, pentachlorophenol, and phenol [28][29][30]. The major advantageous features of the magnesium-based system are: high negative reduction potential of Mg 2+ /Mg 0 (−2.2 V) as compared to Fe 2+ /Fe 0 (−0.44 V, respectively); high solubility of magnesium hydroxide, reduced passivation of metal as compared to iron and no requirement for creating anaerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Cagnola et al (2004) reiterated the advantages of supported catalyst complexes compared to homogenous systems because of easy separation from the treated solution [45]. Morales et al also observed that Pd supported on alumina could be easily recovered compared to the unsupported bimetallic systems [37]. However commercially available immobilized palladium catalysts such as palladium supported on carbon or Pd-alumina are very costly.…”
Section: Immobilized Noble Metals For the Deg-radation Of Pollutantsmentioning
confidence: 99%